Study of Passive CMOS Mixers Effects on Image Rejection Ratio - Morte, Jorge; Martínez Pérez, Antonio D.; Aznar, Francisco; Sánchez-Azqueta, Carlos; Celma, Santiago (Jornada de Jóvenes Investigadores del I3A, 2017)
In this brief, modeling and simulation of quadrature passive mixers are analyzed, focusing on the impact they have on the image rejection ratio (IRR). For this purpose, a 65-nm CMOS technology is used.